Anatomi Laporan Keuangan Bank Bermasalah Sebelum Pencabutan Ijin Usaha - Hasan Ashari; Trinandari P Nugrahanti (Department of Accounting-Faculty of Economic and Business (FEB), 2020)
This research based on the many problematic rural banks (BPR) in Indonesia and had declared as failing banks those their business licenses had revoked by the bank supervisory authority. This paper aims to explain the conditions that occurred in the last years of a BPR before experiencing failure and to analyze the causes of this condition based on interviews with practitioners who had taken handle failed bank resolutions and references and financial indicators in the BPR. The bank condition is seen based on the financial reports for the last two years submitted by the BPR to the bank supervisory authority. This research was conducted by conducting interviews, studying literature, and analyzing the main financial ratios of banks by taking a sample of 31 rural banks whose business licenses had been revoked by the bank supervisory authority. The concluding of this study is mismanagement is the main factor that has impacted increasing of Non-Performing Loan (NPL), Operating Expense to Operating Income (OEOI), and Loan to Deposit Ratio (LDR), it Also has consistently decreasing Capital Adequacy Ratio (CAR) and Return on Asset (ROA).